2009
DOI: 10.1186/1757-1626-2-9346
|View full text |Cite
|
Sign up to set email alerts
|

Wegener's granulomatosis presenting as an abdominal aortic aneurysm: a case report

Abstract: IntroductionAortic aneurysm is not common in young patient. When a young patient presents with abdominal aortic aneurysm, there may be an underlying cause.Case presentationHere, we describe a case of a 33-year-old gentleman who presented with flu like illness, chest and abdominal pains following a tooth extraction. A chest X-ray and subsequent computerised tomogram of the chest and abdomen demonstrated lung nodules and an abdominal aortic aneurysm. The aneurysm was repaired and his serology was positive for We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…In one case, the patient died from aortic dissection. 3 In one case, 1 the patient was treated medically. This patient was diagnosed with WG assuming that the periaortitis, as seen on CT scan was caused by WG, without pathologic confirmation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In one case, the patient died from aortic dissection. 3 In one case, 1 the patient was treated medically. This patient was diagnosed with WG assuming that the periaortitis, as seen on CT scan was caused by WG, without pathologic confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…In another case, no histology was obtained because the specimen was lost. 3 The diagnosis of WG is based on four clinical criterions as defined by the Chapel Hill Consensus Conference in 1994. These are nasal or oral inflammation, abnormal chest radiograph (showing the presence of nodules, fixed infiltrates, or cavities), abnormal urinary sediment (microscopic hematuria), and granulomatous inflammation on biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CT is an extremely accurate tool for both diagnosis and sizing of aortic aneurysms [5-9]. A longitudinal cohort study of GPA patients evaluated at the U.S. National Institutes of Health between 1968 and 1992 demonstrated that 91% experienced clinical improvement and 75% entered complete remission when treated with cyclophosphamide and methylprednisolone [7]. A meta-analysis revealed that pulse cyclophosphamide is less toxic than continuous cyclophosphamide but may be associated with a higher relapse rate [5].…”
Section: Discussionmentioning
confidence: 99%
“…However, a review of the literature revealed a number of cases in which the involved arteries included the aorta [66][67][68][69][70][71][72][73][74], gastric [75], subclavian [76], pulmonary [74] and internal carotid artery [39]. In most instances, depending on the artery affected, abdominal pain was the presenting symptom [66,68,[70][71]. In other cases, back pain [69,72], arm pain [76], headache due to subarachnoid hemorrhage [39] and atrioventricular block were the presenting symptoms.…”
Section: Large Vessel Vasculitis With or Without Aneurysm Formationmentioning
confidence: 99%